Protective Effects of N-Acetylcysteine in Concanavalin A-Induced Hepatitis in Mice - Chengfen Wang; Yujing Xia; Yuanyuan Zheng; Weiqi Dai; Fan Wang; Kan Chen; Jingjing Li; Sainan Li; Rong Zhu; Jing Yang; Qin Yin; Huawei Zhang; et al. (Hindawi Limited, 2015)
This study was designed to study the protective effects and mechanisms of N-acetylcysteine (NAC) in concanavalin A-induced hepatitis in mice. In this study, pretreatment with NAC ameliorated the histopathological changes and suppressed inflammatory cytokines in ConA-induced hepatitis. The expression of IL-2, IL-6, TNF-α, and IFN-γ was significantly reduced in the NAC-treated groups. NAC activated PI3K/Akt pathway and inhibited the activation of NF-κB. Additionally, NAC reduced autophagosome formation, as assessed by detecting the expression of LC3 and Beclin 1. Our results demonstrate that NAC can alleviate ConA-induced hepatitis by regulating the PI3K/Akt pathway and reducing the late stages of autophagy. Our results described a new pharmaceutical to provide more effective therapies for immune hepatitis.